Thinking Process Profile of Senior High School Students in Physics Problem-Solving: Terms of Differences in Emotional Intelligence Levels and Gender - Binar Kurnia Prahani; Wahyu Hari Kristiyanto; Joko Siswanto; Budiyono Saputro; Husni Mubarok (Berkala Ilmiah Pendidikan Fisika, 2021)
This literature study aims to obtain the thinking process profile of senior high school students in physics problem-solving based on differences in emotional intelligence levels and gender. In this study used literature study method with phenomenological analysis, functionalism analysis, and critical analysis. The sources used to compile this article include some literature on emotional intelligence, gender effect, thinking process, problem-solving, and several empirical study on students in physics problem-solving, especially in senior high school. The authors summed up the conclusions based on the results of the literature study as follows: (1) The profile of the thinking process is influenced by emotional intelligence level and gender; (2) Emotional intelligence is directly proportional to the thinking process of students in the process of solving physics problems; (3) Students who have high emotional intelligence are more likely to have high physics problem-solving skills; (4) Gender differences (male and female) in solving physics problems, generally, are still debatable, in which sense is it better? Then it further research needs that is valid and reliable to answer this question. (5) There is a strong tendency that the male gender is more resilient in dealing with and solving complex physics problems; (6) The gender of female students is superior in solving physics problems that require very high detail. The main implication of this article is to obtain the thinking process profile of senior high school students in physics problem-solving based on terms of differences in emotional intelligence levels and gender.